SPECIFIC FEATURES OF THE ACTIVITIES OF MINISTER ALISHER NAVOI - Mashrabalieva Durdona Marufjon kizi (Scholars Digest Publishing, 2023)
This article provides brief information about the life and work of the thinker, poet, statesman Alisher Navoi, his work and the good works he did for the improvement, construction and peace of the country.
Keywords: Khurasan, Kherat, Sabzavor, Mashkhad, Marv, Astraabad cities, Ikhlosiya, Nizomiya, Khusravia madrasas, Khalosiya, Fonia khanaqahs, Shifaiya hospital, “Dar ul-Huffaz” reading room.